2021
DOI: 10.1007/s13659-020-00291-9
|View full text |Cite
|
Sign up to set email alerts
|

The Outlook of the Development of Innovative Products from Biocompatible Natural Spider Silk in the Beauty Thread-Lifting Industry

Abstract: Embedding thread lift rhytidectomy, also known as “thread lifting” in China, with the natures of simple operation, less trauma and quick recovery, is progressively used in clinical practice as a new technology of face lifting. Herewith, a brief introduction of the previous advances of thread lifting techniques and materials in the facial beauty industry, combined with the discussion on various types of sutures, common complications, and the site of actions were provided. The main limitations of present thread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This method entails compressing a thicker thread material than the indicated size of the thread product using a sculpt cutter shaped like the cog pattern. Unnecessary parts are then trimmed and sculpted out from the thicker thread material, essentially stamping out the cogged pattern (Figure 7) [38,39]. Manufacturing process of injection molding-type cogged thread.…”
Section: Thickness Of Thread: Tensile Strengthmentioning
confidence: 99%
“…This method entails compressing a thicker thread material than the indicated size of the thread product using a sculpt cutter shaped like the cog pattern. Unnecessary parts are then trimmed and sculpted out from the thicker thread material, essentially stamping out the cogged pattern (Figure 7) [38,39]. Manufacturing process of injection molding-type cogged thread.…”
Section: Thickness Of Thread: Tensile Strengthmentioning
confidence: 99%
“…It was reported that they can be used in lithium-ion batteries to retain the capacity and decrease the volume expansion of silicon ( Choi and Choy, 2020 ), for aerospace application ( Mayank et al, 2021 ), as vision-based vibration sensors ( Liu et al, 2020a ), silk-based humidity sensors ( Liu et al, 2020b ), or protein-based adhesives for transparent substrates ( Roberts et al, 2020 ). In addition, application of spider silk proteins in the cosmetic industry has been explored recently, for example as a new technology for face lifting ( Qing et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%